SIZE DISTRIBUTION OF PENAEID PRAWN SEED IN THE KALI ESTUARY, KARWAR - Gunaga, Vishnudas; Neelakantan, Kusuma; Neelakantan, B (Indian Journal of Fisheries, 2011)
Penaoid prawn seeds were collected QMovcmbcr, 1986 - November, 1987) from 5 stations in the Kali estuary to study the size distribution of different species. The population was mainly composed of specimens with modal size at 6 - 10 mm. Since the same size groupw repeatedly dominated in the majority of the months, no inference could be drawn on the growth rate. An attempt was also made to determine the breeding seasons of different species of pcnacid prawns based on the seasonal abundance of postlarvae in the Kali estuary. INTRODUCTION